Social Discrimination and Health Care: A Multidimensional Framework of Experiences among a Low-Income Multiethnic Sample. Issue 3 (3rd April 2018) - D'Anna, Laura Hoyt; Hansen, Marissa; Mull, Brittney; Canjura, Carol; Lee, Esther; Sumstine, Stephanie
ABSTRACT: The study aims to describe the perceived discriminatory health care treatment experiences and its impact on care among minority urban-dwelling adults. Semistructured qualitative interviews (N = 51) were conducted with patients from community-based health care settings, and systematic, grounded theory approach was used. Three distinct themes emerged: (a) the sources of discriminatory experiences, (b) its impact on health care, and (c) the provider/organization recommendations to address discriminatory practices. The study highlights the relevance of perceived discrimination in avoidance of health care services, nonadherence to treatment, and adverse health-related sequelae by low-income urban-dwelling adults with little access to health care.